IFRS adoption, institutional quality and foreign direct investment inflows: a dynamic panel analysis - Owusu, Godfred Matthew Yaw; Mohd Saat, Nur Ashikin; K. Suppiah, Susela Devi; Law, Siong Hook (Faculty of Business and Accountancy, University of Malaya, 2017)
Research aims: This study examines whether developing countries that had adopted the International Financial Reporting Standards (IFRS) experience better foreign direct investment (FDI) inflows than non-adopting countries. Linked to that, the study also examines the moderating role of country-level institutional quality in the relationship between IFRS adoption and FDI inflows. Design/ Methodology/ Approach: A panel data of 116 developing countries covering the period of 1996 to 2013 was used for the empirical analysis. The efficient two-step System Generalised Method of Moments (GMM) estimation technique with Windmeijer corrected standards errors and orthogonal deviations was employed to examine the dynamic empirical relations. Research findings: Results demonstrate that IFRS adoption, on its own, does not affect the amount of FDI inflows to developing countries. However, from the interaction noted between IFRS adoption and institutional quality, it is observed that countries that adopted the IFRS experience better FDI inflows when the institutional quality is present. Theoretical contribution/ Originality: This study extends knowledge on the IFRS-FDI nexus by examining the role of institutional quality in the relationship. Practitioner/ Policy implication: The findings of this study suggest that the decision to adopt the IFRS should not be undertaken as a stand-alone strategy. Instead, it should be taken in tandem with other institutional reforms which are aimed at improving institutional quality. Research limitation/ Implications: Developing countries that have adopted the IFRS as well as those that are planning to adopt it should therefore, consider pursuing rigorous institutional developmental reforms as a means of complementing their adoption decision.